Blurring Boundaries in Coworker Relationships: How a Nonwork Setting Becomes a Relational Holding Environment - Schinoff, Beth S.; Pillemer, Julianna; Rogers, Kristie M.; Petriglieri, Jennifer Louise (Organization Science, 2025)
Positive work relationships often emerge when coworkers blur the boundaries of their work and nonwork lives in their interactions. A growing body of scholarship suggests that such boundary blurring increasingly occurs in a variety of nonwork settings. However, existing research has drawn mixed conclusions about whether boundary-blurring interactions in nonwork settings lead to beneficial or detrimental outcomes for coworker relationships. Through an inductive study of users of the exercise platform Peloton, we build theory on how and why a nonwork interaction setting facilitates work-nonwork boundary blurring that leads to positive work relationships. Our findings demonstrate that informants perceive Peloton as having a unique set of characteristics that filters out the discomfort of interacting with coworkers in a nonwork setting and provides them with new ways of understanding the potential of their coworker relationships. These two processes enable Peloton to function as a relational holding environment or — a social context that reduces uncomfortable relational affect and facilitates relational sensemaking. Experiencing Peloton as a relational holding environment motivates informants to deepen their existing positive relationships and forge a broader set of positive relationships across work-related silos. Our theory advances scholarship on work-nonwork boundaries, positive work relationships, and the psychodynamic literature on holding environments. It also has important implications for how managers and employees navigate social contexts to facilitate positive work relationships.